Interpretation and Perception of Two Different Kumite Fighting Intensities through an Integrated Approach Training in International Level Karatekas: An Exploratory Study. Issue 2 (October 2015) - Invernizzi, Pietro Luigi; Longo, Stefano; Bizzi, Marica; Benedini, Stefano; Merati, Giampiero; Bosio, Andrea
"Small sided games, " used effectively in many team sports as a form of training, can be mimicked in combat sports by fighting at different subjective intensities, based on adjectives proposed by coaches. This approach could aim at improving aerobic performance by using specific techniques. Nevertheless, an adequate perception of intensity is crucial. The aim of the study was to verify the ability of karatekas to interpret and perceive two different intensities during this integrated approach. Ten international level karatekas ( M age=18 yr., SD = 3, range = 16–25) were asked to fight four matches (2 min. each) either at low or highest intensity. Physiological (heart rate, blood lactate) and perceptual (perceived effort) responses were different between intensities. However, physiological responses at low intensity were higher than expected and did not match effort perception. This could be attributable to the presence of an opponent, which probably raised the level of effort through a competitive component. At the highest intensity, physiological responses were similar to official competitions and other specific training protocols, whereas perceptual responses were higher than values found in literature.